Simplified implementation of the Heckman estimator of the dynamic probit model and a comparison with alternative estimators - Wiji Arulampalam; Mark B. Stewart (Institute for the Study of Labor (IZA), 2007)
This paper presents a convenient shortcut method for implementing the Heckman estimator of the dynamic random effects probit model using standard software. It then compares the three estimators proposed by Heckman, Orme and Wooldridge based on three alternative approximations, first in an empirical model for the probability of unemployment and then in a set of simple simulation experiments.
Keywords: 330; Dynamic discrete choice models; initial conditions; dynamic probit; panel data; Probit-Modell; Diskrete Entscheidung; Panel; Schätztheorie; Vergleich; Arbeitslosigkeit; Simulation; Theorie